FOCUSING ON COMPETENCE AS A STRATEGY TO TEACH ESP IN CONTENT AND LANGUAGE INTEGRATED LEARNING CONTEXTS - Contero Urgal, Candela (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
The increasing spread of bilingual programs in Spanish Universities has had to face multiple worries and uncertainties over the success of Content and Language Integrated Learning (CLIL) and English-medium instruction (EMI) plans (Pavón, 2018). One of these concerns addresses the question of whether content or language should prevail in CLIL teaching. Content teachers worry about giving more importance to language than to the content they need to teach, fearing they will not be able to cope with all the compulsory content during their lectures (Doiz, Lasagabaster Pavón, 2020). CLIL developers have had to fight against the pessimistic opinions towards CLIL and its implementation in Higher Education (Cañado, 2020). The present paper aims to meet the need to move towards competence development in CLIL teaching. Approaching language and content teaching through a competence-focused perspective will help us tackle interdisciplinary as well as sustainable development goals through CLIL. A survey conducted on students of Business English courses within CLIL and Non-CLIL contexts will help us envisage the usefulness of adding non-linguistic skill development to English for Specific Purposes of teaching as a way to bridge the gap between language and content.